(untitled) (Journal of the College of Basic Education, 2022)
The inverse problem is important method in the design of electrostatic lenses which is used in this work, with new technique by suggesting an axial electrostatic potential distribution using polynomial function ,the paraxial ray equation was solved to obtain the trajectory of the particles that satisfies the suggested potential function, the Finite-Element Method (FEM) is used in the solution of Laplace’s equation for determine the axial potential . The results showed low values of spherical and chromatic aberrations comparing with other searches about( 3.9) for spherical aberration and(0.24) of chromatic aberration for good lens’s design. values of potential of 10